Sinergitas Komunikasi Interpersonal antara Owner Toko Fariz Fashion Padangsidimpuan dengan Karyawan - Siregar, Sulaiman Al Farizy; Sazali, Hasan (Communication & Social Media, 2022)
This article aims to discuss the synergy of interpersonal communication between the owner of the Fariz Fashion Padangsidimpuan shop and the employees. Interpersonal communication synergy is a plan that has been chosen to interact with someone with actions to be taken to achieve a common goal, synergy is also a method used to minimize bad actions in managing a business to be achieved. The research conducted by the author is a field research (field research), with a qualitative descriptive research nature, in order to provide clarity on the problem or event under study so that the population in this study are the owners and employees. The sampling was carried out using the interview method, namely by taking samples from the questionnaire as a whole with a total of 11 people, 3 employees, 1 shop owner and 7 customers. The results of the study indicate that the strategy is the initial stage of starting the strategy by compiling the rules of duties and responsibilities as employees, the second implementation of the strategy is the implementation of the strategy that has been formulated in the early stages.